Influence of technology temperature on the fatigue cracking resistance of asphalt mixtures used for bridge pavement - Radziszewski, Piotr; Plewa, Andrzej; Kowalski, Karol; Król, Jan; Sarnowski, Michał; Pokorski, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Bridges are an integral part of road infrastructure. In times of the roadnetwork expansion in Poland a lot of bridges were constructed. Due to the nature of work, a bridge structure should comply with specific features and requirements. This article presents the results of the fatigue life of selected asphalt mixtures used in bridge structures. Mixtures for various pavement layers were investigated. The effect of high temperature on stiffness modulus and fatigue cracking resistance with different levels of strain were analyzed. These relationships were presented in the regression equations form. The crucial influence of increased technology temperature on asphalt mix fatigue life was proved.